Antimicrobial resistance patterns of urinary tract infection organisms isolated from pregnant women’s urinary samples at lancet clinical laboratories in Zimbabwe, 2021 - Mahamane Salissou, Maibouge Tanko (Journal of Midwifery, 2023)
Worldwide, bacterial infections are a main cause of morbidity and mortality, mainly in low-income countries. The world emergence of antimicrobial resistance negatively impact the management of infectious diseases. Nationwide, there is an increasing concern over antimicrobial resistance (AMR) recently evaluated to contribute for more than 700,000 deaths per year across the globe. The key objective of this present study is to characterise the antimicrobial resistance patterns of urinary tract organisms isolated from pregnant women’s urinary samples analysed at Lancet Clinical Laboratories in Zimbabwe from January to December 2021. This was a laboratory based, cross sectional study conducted among pregnant women’s samples analysed at the laboratory. Microbiology results logbook and patients’ clinical data were used to evaluate basic descriptive statistics (proportions and mean) of participants engaged in this study. We describe the characteristics of variables of respondents where categorical variables were portrayed in the form of numbers and percentages in table, figures format. The prevalence of UTI was 60% with the main isolated bacteria being Escherichia coli (28.10%), Staphylococcus aureus (9.18%) and Kleibseilla pneumoniae (10.27%). There was association between gestational ages with UTI. The prevalence of AMR was 54%. The highest resistant drugs being Ampicillin (60%), Vancomycin (45%) and Penicillin (40%), the least resistant were chloramphenicol (15%), ciprofloxacin (23%) and nitrofurantoin (25%). The prevalence of AMR was high with regards   to AMR prevalence rates in a study conducted in Zimbabwe Bulawayo. This is mainly due to the misuse of drugs therefore re-enforcement of prescription-only policies is crucial.